Analisis Epidemiologi dan Penyebab Kejadian Luar Biasa (KLB) Keracunan Makanan di Puskesmas Ngombol: Studi Kasus Keracunan Makanan Akibat Staphylococcus aureus - ikrila, ikrila; Widjanarko, Bagoes; fauzi, muh; Sutiningsih, Dwi; Chomariyah, Zumrotul (Jurnal Epidemiologi Kesehatan Komunitas, 2025)
Background : On Saturday, July 12, 2024, there was an Extraordinary Event (KLB) of food poisoning at a mini workshop event at Ngombol Community Health Center, Purworejo Regency. A total of 57 people experienced symptoms of poisoning after consuming the food provided. An investigation was conducted to identify the source of the outbreak and associated risk factors.Methods : The investigation was conducted using a cross-sectional study design. Data were collected through a questionnaire containing information on risk factors and clinical signs and symptoms. A total of 65 event participants were sampled in this investigation. Analysis was descriptive, and attack rates were calculated for each factor. Samples of food waste (rice, chicken rica-rica, pickles, noodles and crackers) were collected for laboratory examination.Result : Of the 65 people, 57 experienced symptoms of diarrhea (100%), abdominal cramps (100%), fever (52.1%), vomiting (72.4%), and nausea (68.4%). %). Most cases were detected in women (92.6%) with an age range of 26-56 years (average 28 years). The incubation period was between 6-10 hours (mean 8 hours). The investigation showed that people who ate rica-rica chicken were sick (57/65; Attack Rate 87.6%). Laboratory tests of feces showed positive Staphylococcus aureus.Conclusion : The cause of the food poisoning was chicken rica-rica contaminated with Staphylococcus aureus. The contamination may have occurred due to prolonged storage of the food, from processing on Thursday afternoon (6 p.m.) to serving on Friday afternoon (1 p.m.).